SURVEY OF LEARNING PHYSICAL EDUCATION FOR SPORTS AND HEALTH IN THE COVID19 ERA AT MTS NEGERI 1 BOYOLALI ACADEMIC YEAR 20202021 - Aroh Abatin; Hanik Liskustyawati; Abdul Aziz Purnomo Shidiq (Universitas Sebelas Maret, 2021)
This study aims to determine: (1) the implementation of assessments by teachers of students during the Covid-19 era PJOK learning at MTs Negeri 1 Boyolali in the 2020/2021 school year; (2) constraints faced by teachers in learning PJOK in the Covid-19 Era at MTs Negeri 1 Boyolali in the 2020/2021 school year; (3) the level of student interest in learning in the Covid-19 era PJOK at MTs Negeri 1 Boyolali in the 2020/2021 school year; (4) the obstacles faced by students in learning PJOK in the Covid-19 Era at MTs Negeri 1 Boyolali in the 2020/2021 school year. This research uses qualitative research methods with survey techniques. The research samples were teachers and students of MTs Negeri 1 Boyolali who were domiciled. The subjects of this study included 5 PJOK teachers and 105 students out of 1041 people based on the Stratified Random Sampling. Data collection techniques with questionnaire techniques (questionnaire). The results of this study are as follows: (1) The implementation of an assessment by the teacher of students during the Covid-19 era PJOK learning at MTs Negeri 1 Boyolali, which is carried out well in terms of attitudes, aspects of skills and aspects of knowledge because the teacher has a strategy in implementing the assessment at each aspect as well as the teacher's awareness that these three aspects are equally important in learning PJOK; (2) The constraints faced by the teacher in learning PJOK in the Covid-19 Era at MTs Negeri 1 Boyolali, in the learning preparation stage in the form of difficulties in making various materials and planning learning equipment, for the learning process stage the teacher experienced dissatisfaction and discomfort in delivering learning PJOK online, teachers find it difficult to monitor and provide direction for each participant; (3) The level of interest in students' learning towards Covid-19 Covid-19 PJOK Learning at MTs Negeri 1 Boyolali, from the indicators of happy feelings driven by sincerity and enthusiasm when participating in learning, from indicators of interest driven by the desire to achieve achievement in learning outcomes, awareness of the importance of health, hobbies , and can increase self-confidence, and for indicators of student involvement attentively and material can be accessed before and after learning; (4) The constraints faced by students in learning PJOK in the Covid-19 Era at MTs Negeri 1 Boyolali, in the learning opening process is the difficulty of finding learning resources, when the core process of students is less interacting with teachers and friends, and when learning closes participants students cannot overcome difficulties even though the teacher has provided solutions.